Macroeconomic Impact of the Itaipu Treaty Review for Paraguay - Che, Natasha (Washington, D.C. : International Monetary Fund, 2021)
With the debt obligation of Itaipu Binational being completed paid off by 2023, the Annex C of the Treaty of Itaipu, which governs the operation and revenue distribution of the Itaipu Dam, is due for review and possible revisions. The implications for Paraguay's export revenues and fiscal position are potentially significant. The paper reviews the current energy distribution and sales arrangements of Itaipu and the potential implication of the Annex C revision for the future.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Electric Utilities; Foreign Exchange; Informal Economy; Trade; Underground Econom